Public Relations : the profession and the practice - Lattimore, Dan. (New York : McGraw-Hill, 2013)
"Public relations has developed as a major force in a growing, global information society. The practice of public relations is changing to include new, interactive media, while continuing to depend on the foundation of traditional media. The multi-disciplinary approach to understanding public relations is provided by the authors who come from business, journalism, communication and advertising backgrounds. The easy-to-read style of the text has been a hallmark of the text from its beginning. It includes spotlights on important topics or issues, mini-cases with short real-life cases, and end-of-the-chapter case studies often of major events such as the BP crisis, or GM's financial crisis where it used social media to provide interactive relationships with its constituencies"--
Machine generated contents note: Preface -- About the Authors-- Visual Preview -- Part I: THE PROFESSIONChapter 1. The Nature of Public RelationsChapter 2. The History of Public RelationsChapter 3. A Theoretical Basis for Public RelationsChapter 4. Law and EthicsPart II: THE PROCESSChapter 5. Research: Understanding Public OpinionChapter 6. Strategic Planning for Public Relations EffectivenessChapter 7. Action and CommunicationChapter 8. Evaluating Public Relations EffectivenessPart III: THE PUBLICSChapter 9. Social and Traditional Media RelationsChapter 10. Employee CommunicationChapter 11. Community RelationsChapter 12. Consumer Relations and Marketing Chapter 13. Investor RelationsPart IV: THE PRACTICEChapter 14. Public Affairs: Relations with GovernmentChapter 15. Public Relations in Nonprofit OrganizationsChapter 16. Corporate Public RelationsAppendix 1: Writing A-1Appendix 2: Speechmaking A-9Appendix 3: Video Production.
Includes bibliographical references and index.
Keywords: Public relations; Public relations -- United States